Early Clinical and Economic Outcomes for the VELYS Robotic-Assisted Solution Compared with Manual Instrumentation for Total Knee Arthroplasty - Huang, Philip; Cross, Michael; Gupta, Anshu; Intwala, Dhara; Ruppenkamp, Jill; Hoeffel, Daniel (The Journal of Knee Surgery, 2024)
Robotic-assisted total knee arthroplasty (TKA) has been developed to improve functional outcomes after TKA by increasing surgical precision of bone cuts and soft tissue balancing, thereby reducing outliers. The DePuy Synthes VELYS robotic-assisted solution (VRAS) is one of the latest entrants in the robotic TKA market. Currently, there is limited evidence investigating early patient and economic outcomes associated with the use of VRAS. The Premier Healthcare Database was analyzed to identify patients undergoing manual TKA with any implant system compared with a cohort of robotic-assisted TKAs using VRAS between September 1, 2021 and February 28, 2023. The primary outcome was all-cause and knee-related all-setting revisits within 90-day post-TKA. Secondary outcomes included number of inpatient revisits (readmission), operating room time, discharge status, and hospital costs. Baseline covariate differences between the two cohorts were balanced using fine stratification methodology and analyzed using generalized linear models. The cohorts included 866 VRAS and 128,643 manual TKAs that had 90-day follow-up data. The rates of both all-cause and knee-related all-setting follow-up visits (revisits) were significantly lower in the VRAS TKA cohort compared with the manual TKA cohort (13.86 vs. 17.19%; mean difference [MD]: −3.34 [95% confidence interval: −5.65 to −1.03] and 2.66 vs. 4.81%; MD: −2.15 [−3.23 to −1.08], respectively, p-value < 0.01) at 90-day follow-up. The incidence of knee-related inpatient readmission was also significantly lower (53%) for VRAS compared with manual TKA. There was no significant difference between total cost of care at 90-day follow-up between VRAS and manual TKA cases. On average, the operating room time was higher for VRAS compared with manual TKA (138 vs. 134 minutes). In addition, the discharge status and revision rates were similar between the cohorts. The use of VRAS for TKA is associated with lower follow-up visits and knee-related readmission rates in the first 90-day postoperatively. The total hospital cost was similar for both VRAS and manual TKA cohort while not accounting for the purchase of the robot.
Keywords: robotic surgery; total knee arthroplasty; VELYS; VRAS; real world data